Impact of counselling on selecting a hormonal contraceptive method - Patel, Darshna M.; Salat, Vandita K.; Patel, Mahesh M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Unmet need for family planning is an important indicator for assessing the demand for family planning services. As per NFHS-4, the contraceptive prevalence rate in women age 15-49 years was 53.5 % and the unmet need for family planning among married women was 12.9%. Counselling provides the Health care professionals (HCPs) an opportunity to understand the individual need of a contraceptive seeker. Methods: This was a cross-sectional, observational study conducted at GMERS hospital, Valsad during June 2017 to October 2017. Sexually active women of 18 to 40 years who consulted HCPs for contraception and who interested in starting hormonal contraceptive method or expressed interest in switching (changing) to hormonal methods were included in the study. Total 213 women were enrolled in the study. Questionnaires with information on the women’s pre- and post-counseling contraceptive choice, her perceptions, and the reasons behind her post-counseling decision were filled both by the HCP and the participating women. The completed questionnaires were collected and analyzed. Results: During pre-counseling, most common hormonal contraceptive method selected by women was combined hormonal contraceptive pills followed by DMPA, LNG-IUS and POPs. In present study, structured contraception counseling helped most women (97.2 %) to choose a contraceptive method. There were statistically significant differences in choice of contraceptive methods during pre and post-counseling except COCs. Among hormonal contraceptive methods, maximum difference was observed for choice of the COCs after counseling as compared to pre-counseling. Counseling helped more than 90% of the women who were indecisive to choose any contraceptive method. More than three fourth of them opted for hormonal methods with a maximum selection of COCs. The most common reasons for selecting COCs was ease of use for COC, breast feeding for POP and the most common reasons for not choosing other available contraceptive methods was discussion with partner. Conclusions: The combined hormonal contraceptive pills were reported to be the most commonly used contraceptive method. There were statistically significant differences in choice of contraceptive methods during pre and post-counseling with maximum difference in COCs. Counseling helped most of the women who were indecisive to choose any contraceptive method.